Cartoon violence: A comparison of past and present - Macias, Elizabeth Cameron (2010)
This study examined four cartoons in order to determine the extent of the violence, type of violence, and the context of violence in both dated and modern cartoons. To achieve this goal a content analysis of 'The Flintstones', 'The Jetsons', 'The Simpsons' and Family Guy' was performed. These shows were chosen based on their popularity, classification as family programming, and the influence they have had on American culture